2017
DOI: 10.18632/oncotarget.14545
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cell migration is inhibited by a novel therapeutic strategy antagonizing the alpha-7 receptor

Abstract: A 14mer peptide (T14) derived from the C-terminus of acetylcholinesterase (AChE) selectively activates metastatic breast cancer cells via the alpha-7 nicotinic receptor (α7 nAChR). This naturally occurring peptide is also present in brain, is elevated in Alzheimer's disease, and is antagonised by a cyclized variant (NBP-14). Here we investigated the effects of NBP-14 in six different cancer cell lines, primary leukemia B-cells and normal B-cells. All cells tested expressed α7 nAChR, intracellular and extracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…; Zhao, ; Pepper et al . ). Thus, interference with α7 protein expression or treatment with specific inhibitors can reverse proangiogenic effects of nicotine and inhibit cancer cell growth (Wu et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Zhao, ; Pepper et al . ). Thus, interference with α7 protein expression or treatment with specific inhibitors can reverse proangiogenic effects of nicotine and inhibit cancer cell growth (Wu et al .…”
Section: Introductionmentioning
confidence: 97%
“…; Pepper et al . ). Thus, selective antagonists or NAMs that could specifically target the overexpressed α7 would be good candidate drugs.…”
Section: Introductionmentioning
confidence: 97%
“…Two papers just published would at first glance have little in common: one features a novel approach to combating metastases [1] whilst the other suggests a new strategy for treating Alzheimer's, [2]. Nonetheless, here we describe a possible link based on the concept that both cancer and neurodegeneration are inappropriately activated forms of development, and in both cases could be mediated by the same bioactive peptide acting at the same receptor.…”
mentioning
confidence: 99%
“…Interestingly enough, a similar signalling system could be operational in metastases: studies with breast cancer cell lines have shown an enhancement of metastatic cell activity in response to peptide treatment, in a calcium and α7-nAChR dependent manner [5]. Most recently we have demonstrated that AChE-pept ide could indeed play a pivotal role in cell migration, with its action blocked by interception at the level of the α7-nAChR [1]. …”
mentioning
confidence: 99%
See 1 more Smart Citation